Should Investment and Financing Decisions Be Separated? - Ferrara, William L. (The Accounting Review, 1966)
Abstract The essential conclusion of this paper is that investment and financing decisions must be kept separate. The ability to identify specific sources of funds with specific investment proposals is, at best, an illusion. This point of view is supported by an argument analogous to that applicable to many joint-cost problems of accounting as well as by the "pool of projects" and the "pool of funds" concepts. Investment decisions should be evaluated by the usual cash-flow techniques, as illustrated in this paper. The decision to finance by alternative methods should be based on the rate of interest to be charged which could legitimately be adjusted for differences in restrictions inherent in alternative sources of borrowed funds. Great care must be exercised to avoid the pitfall of constructing illusory discounted cash-flow differentials which are based upon apparent but not real differences in the amount of borrowings. As for leasing, the essential features of a long-term, non-cancellable lease must be understood; it is partially a method of financing and partially a method of investing. For proper evaluation, the financing aspects should be eliminated at the lowest rate of interest available to the company. With financing eliminated, the lease can then be compared to an outright purchase to determine which is the least costly method of acquiring the services of the equipment or facilities under consideration.